2019
DOI: 10.1002/suco.201900141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating steel fiber‐reinforced self‐consolidating concrete performance

Abstract: The fiber‐reinforced self‐compacting concrete (FR‐SCC) is considered a high‐performance material, clustering characteristics of SCC combined with steel fibers. This paper assessed fresh and hardened state properties of a reference SCC and a FR‐SCC with fibers of three types and three quantities of reinforcement, totalizing 10 mixtures. Fresh state properties of the mixture were evaluated through the tests of slump‐flow, flow rate, filling ability, plastic viscosity by V‐funnel, passing ability by J‐ring and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The presence of steel fibers in the SCC causes the matrix to become disrupted, resulting in more voids that can lead to a reduction in compressive strength. A study indicated that samples containing fibers displayed a decrease in this characteristic for all types and amounts of fiber when compared to a reference mixture of SCC without steel fibers [42]. The concentration of fibers at any sections of the specimen should be avoided not to reduce the system ability to sustain loading capacity.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The presence of steel fibers in the SCC causes the matrix to become disrupted, resulting in more voids that can lead to a reduction in compressive strength. A study indicated that samples containing fibers displayed a decrease in this characteristic for all types and amounts of fiber when compared to a reference mixture of SCC without steel fibers [42]. The concentration of fibers at any sections of the specimen should be avoided not to reduce the system ability to sustain loading capacity.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Kang et al [2] evaluated the influence of pouring direction and fiber distribution characteristics on the bending strength of composite materials. Silva et al [3] demonstrated through experimentation that steel fibers have a significant toughening effect on cement-based materials, and that both flexural strength and toughness increase with increasing fiber length.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of steel fibers in concrete has been highly investigated in the past two decades, and the experimental results have proved its capacity for structural concrete applications. da Silva et al [ 4 ] pointed out that the use of steel fibers enhances the flexural toughness and flexural strength of SCC. Other studies on the addition of steel fibers into concrete confirmed that the splitting tensile strength and modulus of rupture are enhanced as well [ 5 ].…”
Section: Introductionmentioning
confidence: 99%